Thoughts on writing, identity and memory in the Early Iron Age of Southern Portugal (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
The analysis of the rich and diverse funerary record of the southern Portuguese Early Iron Age highlights the development during this period of a variety of identity and representation strategies, based on variable and dynamic combinations of local and exotic elements. The adoption of writing, and in particular the specific and differentiated uses it was given in some areas of southern Portugal, may be understood in the framework of said strategies, and it illustrates the ways in which exogenous elements were adapted to local practices and discourses. In this context, the production of lapidary inscriptions, which are rarely found in other areas of southwestern Iberia, can be interpreted as part of particular processes of (re)construction of collective memory.